2008
DOI: 10.2105/ajph.2007.118505
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Race/Ethnicity Differences in Lead Dose Biomarkers

Abstract: Objectives. We sought to identify predictors of lead concentrations in the blood, tibias, and patellae of older adults and to describe differences by gender, race/ ethnicity, and other factors that can influence lead toxicokinetics and, thus modify health effects.Methods. Participants aged 50 to 70 years (N = 1140) were randomly identified from selected neighborhoods in Baltimore, Maryland. We measured lead concentrations by anodic stripping voltammetry (in blood) and 109 Cd-induced K-shell x-ray fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 74 publications
(63 reference statements)
3
31
0
Order By: Relevance
“…A total of 628 persons were considered current smokers; 526 persons based on the questionnaire and an additional 102 persons based on serum cotinine. Lead exposure also differs with respect to sex (higher in men), race/ethnicity (higher in African Americans), education (higher with lower educational attainment), socio-economic status (higher in lower socio-economic strata), and smoking (higher in smokers) 31, 32…”
Section: Methodsmentioning
confidence: 99%
“…A total of 628 persons were considered current smokers; 526 persons based on the questionnaire and an additional 102 persons based on serum cotinine. Lead exposure also differs with respect to sex (higher in men), race/ethnicity (higher in African Americans), education (higher with lower educational attainment), socio-economic status (higher in lower socio-economic strata), and smoking (higher in smokers) 31, 32…”
Section: Methodsmentioning
confidence: 99%
“…[22-24] Although there is a dearth of data on bone lead in nonwhites, the few existing data suggest that there are larger racial disparities in bone lead compared to blood lead in adults, reflecting the historical disparities in lead exposure. [25,26] Also, higher levels of lead continue to be more prevalent in disadvantaged—including black—populations than in advantaged populations. [19,26] Finally, new research suggests that certain social factors that are more prevalent in black communities may amplify the hypertensive effects of low levels of lead.…”
Section: Lead Hypertension and Racementioning
confidence: 99%
“…A recent study conducted in Baltimore found higher tibia lead levels in African Americans compared with Whites, after controlling for socio-economic status (SES) or other factors (17). The authors suggested that this difference might be due to the higher life-time cumulative exposure to more polluted environments, rather than differences in bone kinetics by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%